Tiktok Sarana Syiar Islam - Wibawa, Darajat; Nur Chidayah, Prita Priantini (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The study aims to identify the favorite Islamic preachers (Da'i) on TikTok, the most popular themes of Islamic preaching on TikTok, and netizens' evaluations of Islamic preaching on TikTok based on their preferences. The research method employed is a descriptive analysis with a qualitative approach. The theories used in this study include Social Action Theory, Phenomenological Theory, and Symbolic Interaction Theory. Based on the percentage results, the most favored preachers according to netizens are, in order, Abdul Somad, followed by Hanan Attaki, Ustadzah Oki Setiana Dewi, and Handy Bonny. Next on the list are Ali Jabar (deceased), Buya Yahya, Kholid Basalamah, and Das'Ad Latif. Regarding the themes, the five most popular topics favored by netizens are, in order, morality (akhlaq), Sufism (tasawuf), Islamic jurisprudence (fiqh), creed (aqidah), and social interactions (muamalah). Netizens' evaluations of the content of Islamic preaching on TikTok are categorized into three groups: positive, neutral, and negative.